Resin composition for fuel cell separator, fuel cell separator, and method for producing fuel cell separator
The resin composition for fuel cell separators, with controlled compression and volatile content, addresses inefficiencies in manufacturing by enabling rapid and stable filling, resulting in high-quality separators with minimal unevenness and resistance.
Patent Information
- Application Number
- JP2024100731
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-06-21
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-06-21
AI Technical Summary
Existing methods for manufacturing fuel cell separators are inefficient due to long filling times into filling containers, leading to variations in filling amounts and high production costs, with issues of aggregation and low production efficiency.
A resin composition for fuel cell separators is developed, containing graphite powder, epoxy resin, a curing agent, and a curing accelerator, with a specific compression degree and low volatile component content, allowing for rapid filling and stable mass distribution, resulting in separators with minimal thickness unevenness and low contact resistance.
The resin composition enables short filling times, reduces variations in filling mass, and produces fuel cell separators with small thickness unevenness and low contact resistance, enhancing production efficiency and quality.
Smart Images

Figure 0007616467000004 
Figure 0007616467000005 
Figure 0007616467000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition for a fuel cell separator, a fuel cell separator, and a method for producing a fuel cell separator. [Background technology]
[0002] The fuel cell separator serves to provide electrical conductivity to each unit cell, ensure passage of fuel and air (oxygen) supplied to the unit cells, and act as a boundary wall separating them. For this reason, fuel cell separators are required to have various properties such as high electrical conductivity, high gas impermeability, high thickness accuracy, chemical stability, heat resistance, and hydrophilicity.
[0003] To meet these performance requirements, early separators were formed by machining graphite plates, but the time required for processing made the separators too expensive. Recently, therefore, a method has been adopted in which carbon powder and thermosetting synthetic resin powder are mixed to make a powdered raw material, which is then placed in the lower die of a press, covered with an upper die, and pressurized and heated by the press to form the separator.
[0004] For example, Patent Document 1 proposes a method of molding a fuel cell separator by filling a filling container with powdered raw material containing a conductive material and a resin, heating and pre-molding the powdered raw material in the filling container, and placing the obtained pre-molded product in a mold separate from the filling container and heating and pressurizing it.
[0005] However, in Patent Document 1, the time required for preparations, from filling a filling container with powdered raw material, to heating it, and then pouring it into a mold, is 3 to 4 minutes, which causes a problem of low production efficiency. Furthermore, if it takes a long time to fill the powdered raw material into the filling container, the powdered raw material will aggregate inside the raw material supply device, making it impossible to fill the specified mass into the filling container. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2006-244937 A Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has been made in consideration of the above circumstances, and aims to provide a resin composition for a fuel cell separator, which can shorten the filling time into a filling container when manufacturing a fuel cell separator, suppress variation in the filling amount, and form a fuel cell separator with little thickness unevenness and low contact resistance, as well as a fuel cell separator and a manufacturing method thereof. [Means for solving the problem]
[0008] As a result of extensive research into achieving the above-mentioned object, the inventors have discovered that a resin composition having a predetermined degree of compression and a predetermined range of content of volatile components having a boiling point of 100°C or less can shorten the filling time into a filling container when producing a fuel cell separator, can suppress variation in the filling amount, and can form a fuel cell separator with small thickness unevenness and low contact resistance, thereby completing the present invention.
[0009] That is, the present invention provides 1. A resin composition for fuel cell separators, comprising graphite powder and an epoxy resin component including a base agent, a curing agent and a curing accelerator, the composition having a compression degree calculated by the following formula of 14.0 to 40.0% and a content of volatile components having a boiling point of 100°C or lower of less than 1.00 mass%; Compressibility (%)=100×(solid bulk density of resin composition−loose bulk density of resin composition) / solid bulk density of resin composition 2. The resin composition for a fuel cell separator according to 1, wherein the resin composition has a loose bulk density of 0.40 to 0.90 g / cc. 3. The resin composition for a fuel cell separator according to 1, wherein the graphite powder has a loose bulk density of 0.35 to 0.70 g / cc. 4. The resin composition for a fuel cell separator according to 1, wherein the base resin is at least one selected from an orthocresol novolac type epoxy resin having an epoxy equivalent of 194 to 215 g / eq and a biphenyl type epoxy resin having an epoxy equivalent of 180 to 200 g / eq. 5. The resin composition for a fuel cell separator according to 1, wherein the curing agent is a phenol novolac resin having a hydroxyl group equivalent of 103 to 106 g / eq. 6. The resin composition for a fuel cell separator according to 1, wherein the curing accelerator is an imidazole compound having a phenyl group at the 2-position. 7. The resin composition for fuel cell separators according to 1, wherein when the resin composition is filled into a filling container to form a fuel cell separator of 300 mm x 400 mm x 1 mm, the filling time into the filling container is less than 120 seconds. 8. The resin composition for fuel cell separators according to 1, in which, when the resin composition is filled into a container to form a fuel cell separator of 300 mm x 400 mm x 1 mm, the variation in the filling mass into the container is less than 2.00% relative to the reference mass. 9. A resin composition for fuel cell separators is molded from a resin composition containing graphite powder, a base resin, a curing agent, and a curing accelerator, the compression ratio calculated by the following formula being 14.0-40.0%, and the content of volatile components having a boiling point of 100°C or less being less than 1.00% by mass, and the thickness unevenness is less than 50 μm and the contact resistance is 7.00 mΩ cm. 2 A fuel cell separator, Compressibility (%)=100×(solid bulk density of resin composition−loose bulk density of resin composition) / solid bulk density of resin composition 10. A method for manufacturing a fuel cell separator having thick and thin sections for forming grooves that serve as gas flow paths on at least a portion of the surface, comprising: a method for producing a fuel cell separator, comprising: a step of introducing a resin composition for a fuel cell separator, the resin composition comprising graphite powder, and an epoxy resin component including a base agent, a curing agent, and a curing accelerator, the resin composition having a degree of compression calculated by the following formula being 14.0 to 40.0% and a content of volatile components having a boiling point of 100°C or less being less than 1.00 mass%, into a mold for a fuel cell separator such that the introduced mass of the resin composition is a volume ratio approximating the volume ratio of the thick portion to the thin portion of the fuel cell separator; Compressibility (%)=100×(solid bulk density of resin composition−loose bulk density of resin composition) / solid bulk density of resin composition 11. A step of filling the fuel cell separator resin composition into a filling container having projections and recesses formed therein that have a volume ratio approximating that of the thick-walled portion and the thin-walled portion of the fuel cell separator; a step of inverting a container filled with the resin composition above a fuel cell separator mold to pour the resin composition into the mold; 11. The method for producing a fuel cell separator according to claim 10, further comprising a step of compression molding the resin composition poured into the mold. to provide. Effect of the Invention
[0010] The resin composition for fuel cell separators of the present invention has a predetermined degree of compression, and the content of volatile components having a boiling point of 100°C or less is adjusted to be within a predetermined range. Therefore, the resin composition has excellent fluidity and filling properties as a powder, requires a short time to be poured into a mold for fuel cell separators, is highly productive, and has little variation in the filling mass poured into the mold. A fuel cell separator obtained by molding the fuel cell separator composition of the present invention having such properties has small thickness variations and low contact resistance. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 is a schematic cross-sectional view showing an example of a resin composition filling device used in the production of a fuel cell separator of the present invention. [Diagram 2] FIG. 2 is a schematic perspective view showing a main part of the filling device of FIG. [Diagram 3] 11 is an explanatory diagram showing a molding process when a pattern is formed on a filled container. FIG. [Figure 4] 13 is an explanatory diagram showing a molding process when no pattern is formed on the filled container. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in further detail below. [Resin composition for fuel cell separator] The resin composition for fuel cell separator according to the present invention contains graphite powder and an epoxy resin component including a base agent, a curing agent, and a curing accelerator, and is characterized in that it has a compression degree calculated by the following formula of 14.0 to 40.0%, and has a content of volatile components having a boiling point of 100°C or less of less than 1.00 mass%. Compressibility (%)=100×(solid bulk density of resin composition−loose bulk density of resin composition) / solid bulk density of resin composition
[0013] In the present invention, the compression degree of the resin composition for a fuel cell separator is 14.0 to 40.0%, and preferably 18.0 to 35.0%. If the degree of compression is less than 14.0%, the time required to fill the resin composition of the present invention into a mold or filling container will be shorter, but on the other hand, the fluidity will be excessive, so that when the resin composition is filled into a mold or filling container, the mass will exceed the standard value or the resin composition will overflow from the mold or filling container, making it impossible to stably fill a mass that results in a volume ratio approximating the volume ratio of the thick parts (thick portions) to the thin parts (thin portions) of a fuel cell separator. If the compression degree exceeds 40.0%, the fluidity of the resin composition of the present invention will be insufficient, so that it will take a long time to fill it into a mold or a filling container, and the mass when filled into the mold or filling container will be less than the reference mass, making it impossible to stably fill a mass that results in a volume ratio approximating the volume ratio of the thick and thin portions of a fuel cell separator. In the present invention, the reference mass refers to the filling mass for forming the thickness of the fuel cell separator according to the design value. In addition, in the present invention, filling "a mass that results in a volume ratio that approximates the volume ratio of the thick and thin portions of the fuel cell separator" refers to filling the portions corresponding to the thick and thin portions of the fuel cell separator thickly and thinly, respectively, when filling a mold or a filling container with the resin composition, so that the amount of the resin composition filled in the portions corresponding to the thick and thin portions of the fuel cell separator is approximately equal to the volume ratio of the thick and thin portions of the fuel cell separator.
[0014] In the present invention, the loose bulk density (g / cc) and hardened bulk density (g / cc) of the resin composition used to calculate the above-mentioned compression degree are measured using a powder tester PT-S manufactured by Hosokawa Micron Corporation. The loose bulk density is measured under conditions of a vibration time of 30 seconds, and the hardened bulk density is measured under conditions of 180 tapping cycles.
[0015] The fuel cell separator resin composition of the present invention may be in any form, such as granular or powdery, so long as it satisfies the above-mentioned compressibility and other requirements, but is preferably in powdery form. The shape of the powder is not particularly limited, and any shape can be used. The particle size is also not particularly limited, but is preferably 700 μm or less, more preferably 600 μm or less. In the present invention, the particle size is a value measured by a wet method using a particle size distribution measuring device (MT3000 manufactured by Microtrack Bell Co., Ltd.).
[0016] The loose bulk density of the resin composition for a fuel cell separator of the present invention is preferably from 0.40 to 0.90 g / cc, and more preferably from 0.45 to 0.85 g / cc. When the loose bulk density is 0.40 to 0.90 g / cc, the resin composition of the present invention has an appropriate fluidity, so that it does not take a long time to fill a mold or a filling container with the resin composition, and the resin composition does not aggregate in a raw material supplying device, so that a predetermined mass can be stably filled.
[0017] The content of volatile components having a boiling point of 100° C. or less contained in the resin composition for fuel cell separator of the present invention is less than 1.00% by mass, and preferably 0.9% by mass or less. If the volatile components are 1.00 mass% or more, the resin composition of the present invention will adhere to the walls of the raw material supplying device or agglomerate within the raw material supplying device, which will result in a long time being required for filling a mold or filling container, and it will be impossible to stably fill a mass that results in a volume ratio approximating the volume ratio of the thick and thin parts of a fuel cell separator. In the present invention, the amount of volatile components having a boiling point of 100°C or less contained in the resin composition is measured under conditions of holding the temperature at 110°C for 10 minutes using an infrared moisture meter FD-660 manufactured by Kett Electric Laboratory.
[0018] The graphite powder used in the present invention is not particularly limited in type, etc., so long as the range of the compression degree of the resin composition of the present invention is satisfied, and either natural graphite or artificial graphite may be used. Examples of artificial graphite include artificial graphite obtained by burning needle coke, artificial graphite obtained by burning lump coke, spheroidized artificial graphite, and artificial graphite the surface of which has been treated with a pitch coat or the like. On the other hand, examples of natural graphite include flake natural graphite, soil graphite, spheroidized natural graphite, and natural graphite the surface of which has been treated with a pitch coat or the like. Any of these graphite powders may be appropriately selected. These graphite powders may be used alone or in combination of two or more kinds.
[0019] The loose bulk density of the graphite powder used in the present invention is preferably 0.35 to 0.75 g / cc, more preferably 0.35 to 0.70 g / cc. When the loose bulk density of the graphite powder is in the range of 0.35 to 0.75 g / cc, the compressibility of the resin composition can be easily adjusted to the range of 14.0 to 40.0%. The loose bulk density of the graphite powder is a value measured using the same apparatus and under the same conditions as the loose bulk density of the resin composition described above.
[0020] On the other hand, the main agent constituting the epoxy resin component is not particularly limited as long as it has an epoxy group, and examples thereof include orthocresol novolac type epoxy resin, phenol novolac type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, biphenyl type epoxy resin, biphenyl aralkyl type epoxy resin, trisphenol type epoxy resin, brominated epoxy resin, dicyclopentadiene type epoxy resin, biphenyl novolac type epoxy resin, etc., which can be used alone or in combination of two or more. Among these, orthocresol novolac type epoxy resin alone, biphenyl type epoxy resin alone, and mixtures thereof are preferred. The epoxy equivalent of the epoxy resin used in the present invention is not particularly limited, but in the case of an orthocresol novolac type epoxy resin, it is preferably 194 to 215 g / eq, and in the case of a biphenyl type epoxy resin, it is preferably 180 to 200 g / eq.
[0021] The hydrolyzable chlorine content of the epoxy resin base material used in the present invention is preferably 450 ppm or less. If the hydrolyzable chlorine content is 450 ppm or less, the crosslink density of the cured product increases, and the heat resistance of the separator obtained is improved. On the other hand, the lower limit is not particularly limited, but since epoxy resins with a hydrolyzable chlorine content of less than 370 ppm are very expensive, the lower limit is preferably 370 ppm in consideration of cost.
[0022] As the curing agent constituting the epoxy resin component, phenolic resin is preferred. Specific examples thereof include novolac type phenolic resin, cresol novolac type phenolic resin, resol type phenolic resin, aralkyl modified phenolic resin, biphenyl novolac type phenolic resin, trisphenolmethane type phenolic resin, etc., which may be used alone or in combination of two or more. Among these, novolac type phenolic resin is preferred. The hydroxyl equivalent of the phenol resin used in the present invention is not particularly limited, but is preferably 103 to 106 g / eq.
[0023] The curing accelerator constituting the epoxy resin component is not particularly limited as long as it accelerates the reaction between the epoxy group and the curing agent, and examples thereof include phosphine compounds, amine compounds, imidazole compounds, etc., among which, in the present invention, it is preferable to use an imidazole compound having an aryl group at the 2-position. Specific examples of the aryl group include a phenyl group, a tolyl group, a naphthyl group, etc., with a phenyl group being preferred. Specific examples of the imidazole compound having an aryl group at the 2-position include 2-phenylimidazole, 2-phenyl-4-methylimidazole, etc. In addition, when an imidazole compound having a short-chain alkyl group such as 2-methylimidazole is used, the curing time may be too fast to achieve uniform molding, whereas when an imidazole compound having a long-chain alkyl group such as 2-undecylimidazole is used, the curing time may be too slow, resulting in a long molding time.
[0024] In addition to the above-mentioned components, the composition used in the present invention may also contain optional components such as an internal mold release agent. The internal release agent may be appropriately selected from various internal release agents that have been conventionally used in molding separators. Specific examples thereof include stearic acid wax, amide wax, montanic acid wax, carnauba wax, polyethylene wax, etc., and these may be used alone or in combination of two or more kinds.
[0025] In the resin composition of the present invention, the blending amounts of the graphite powder and the epoxy resin components (main agent, curing agent, and curing accelerator) are not particularly limited, but the blending amounts are preferably 22 to 40 parts by mass, more preferably 27 to 35 parts by mass, and even more preferably 30 to 33 parts by mass of the epoxy resin components per 100 parts by mass of the graphite powder. By setting the amount of the epoxy resin component within this range, the fluidity of the resin composition becomes appropriate, resulting in good moldability, and a significant decrease in the gas impermeability and electrical conductivity of the resulting fuel cell separator can be prevented. In this case, the curing agent is preferably mixed in an amount of 0.98 to 1.08 equivalents, and more preferably 0.99 to 1.05 equivalents, relative to the base resin. The amount of the curing accelerator used is not particularly limited, and is preferably 0.1 to 5 parts by mass, and more preferably 0.5 to 2 parts by mass, per 100 parts by mass of the mixture of the base agent and the curing agent. Furthermore, when an internal mold release agent is used, the amount used is not particularly limited, but is preferably 0.01 to 3.0 parts by mass, and more preferably 0.05 to 1.5 parts by mass, per 100 parts by mass of the graphite powder.
[0026] In the method for producing a fuel cell separator of the present invention described later, for example, when producing a fuel cell separator having a size of 300 mm x 400 mm x 1 mm, the resin composition for a fuel cell separator of the present invention can reduce the filling time when filling a filling container having a size corresponding to the fuel cell separator (e.g., 300 mm x 400 mm x 3 mm) to less than 120 seconds. The lower limit of the filling time is not particularly limited, but is usually 20 seconds or more. The method for measuring the filling time is as described in the examples described later. For example, when manufacturing a fuel cell separator of the same size as above, the variation of the filling mass when filling a filling container with the fuel cell can be less than 2.00%, preferably 1.98% or less, and more preferably 1.96% or less, relative to the reference mass. The lower limit of the variation is not particularly limited, but is usually 0.10% or more. The method for measuring this variation is also as described in the examples below.
[0027] [Method for producing a resin composition for a fuel cell separator] The resin composition for fuel cell separator of the present invention may be prepared by, for example, mixing the graphite powder, the base material, the curing agent, and the curing accelerator in a predetermined ratio in any order using a mixer such as a planetary mixer, a ribbon blender, a Loedige mixer, a Henschel mixer, a rocking mixer, or a Nauta mixer. When an internal mold release agent is used, the order of compounding the agent is arbitrary. Since the fuel cell separator resin composition of the present invention is in powder form, it is preferable to use raw materials that are also in powder form, which makes it possible to easily prepare the powdered resin composition.
[0028] In producing the resin composition, for the purpose of adjusting the degree of compression to the above-mentioned range or making the content of volatile components having a boiling point of 100°C or less less than a predetermined amount, if necessary, after mixing the respective components, the resulting mixture can be dried, for example, at 30 to 60°C for 1 to 3 hours and pulverized to obtain a resin composition for fuel cell separators. In addition, after mixing the various components, the mixture can be melt-kneaded using a pressure kneader, a twin-screw continuous kneader, an extruder, a heated roll, or the like, cooled, and then the solidified mixture can be pulverized to a predetermined size to obtain a resin composition for fuel cell separators. The heating temperature during melt kneading is not particularly limited as long as it is equal to or higher than the melting point of the epoxy resin and lower than the heat curing temperature, but is preferably 40 to 100° C., and more preferably 50 to 90° C. The heating time is also not particularly limited, but is preferably 1 to 10 minutes, and more preferably 1 to 5 minutes.
[0029] [Fuel cell separator] The fuel cell separator of the present invention is obtained by molding the above-mentioned fuel cell separator resin composition, and has a thickness variation of less than 50 μm and a contact resistance of 7.00 mΩ·cm. 2 is less than.
[0030] The thickness unevenness of the fuel cell separator of the present invention is less than 50 μm, and preferably 49 μm or less. There is no particular lower limit, and the smaller the better, but it is particularly 1 μm or more. In the present invention, the thickness unevenness is a value evaluated by measuring the thickness of the fuel cell separator at 20 points with a micrometer and using the following formula: Thickness unevenness (μm) = Maximum thickness of fuel cell separator - Minimum thickness of fuel cell separator
[0031] The contact resistance of the fuel cell separator of the present invention is 7.00 mΩ cm 2 Less than 6.90 mΩ cm 2The lower limit is not particularly limited, but the smaller the better. 2 That's all. In the present invention, the contact resistance is a value calculated by the method described in the Examples section below.
[0032] [Method of manufacturing fuel cell separator] The fuel cell separator of the present invention can be produced, for example, by putting the above-mentioned fuel cell separator resin composition of the present invention into a predetermined mold and compression molding it. The mold to be used can be a fuel cell separator mold capable of forming a groove portion to be a gas flow path on at least a part of one or both sides of the surface of the molded body. This produces a fuel cell separator having a thick part and a thin part for forming the groove portion to be a gas flow path on at least a part of the surface. In this case, the method for pouring the resin composition into the mold is arbitrary, but it is preferable to pour the resin composition into the mold for a fuel cell separator so that the poured mass is a volume ratio that approximates the volume ratio of the thick and thin portions of the desired fuel cell separator. The conditions for compression molding are not particularly limited, but the mold temperature is 150 to 190° C., and the molding pressure is 30 to 60 MPa, and preferably 30 to 50 MPa. The compression molding time is not particularly limited and can be appropriately set from about 3 seconds to 1 hour, but from the viewpoint of production efficiency, a short time is preferable, and specifically, 40 seconds or less is preferable. After compression molding, the mixture may be further heated at 150 to 200° C. for about 1 to 600 minutes in order to promote thermal curing.
[0033] As described above, the resin composition of the present invention has a predetermined degree of compression and a predetermined range of volatile components having a boiling point of 100°C or less, and therefore has the properties of being able to shorten the filling time into a filling container and suppressing variation in the filling amount within the filling container. Therefore, the resin composition can be particularly suitably used in a manufacturing method such as that disclosed in Patent Document 1, which includes a step of first filling a powder raw material into a filling container and then pouring it into a mold. Therefore, the fuel cell separator of the present invention is preferably manufactured by a manufacturing method including the steps of filling a filling container with the above-mentioned resin composition, which has projections and recesses formed therein that are similar to the volume ratio of the thick and thin parts of the fuel cell separator, turning the filling container filled with the resin composition upside down directly above a fuel cell separator mold to pour the resin composition into the mold, and compression molding the resin composition poured into the mold. In the present invention, the term "a filling container with projections and recesses formed therein that are similar to the volume ratio of the thick and thin parts of the fuel cell separator" refers to a filling container in which recesses corresponding to the thick parts of the fuel cell separator and projections corresponding to the thin parts are formed, and the volume ratio of the recesses and projections is approximately equal to the volume ratio of the thick and thin parts of the fuel cell separator. In this case, the filled resin composition may be premolded by heat treatment before the filled container is turned upside down. The heat treatment conditions are not particularly limited as long as the temperature is higher than the melting point of the epoxy resin and lower than its hardening point, and examples of the heat treatment conditions include heating at 50 to 100°C for 0.5 to 10 minutes.
[0034] Hereinafter, one embodiment of the method for producing a fuel cell separator of the present invention will be described with reference to the drawings. The method for producing a fuel cell separator of the present invention can be carried out using a filling apparatus 10 shown in FIG. 1 and 2, the filling device 10 is configured to include a hopper 11 that holds the resin composition A, a filling container 12 installed under the hopper 11, and a movable table 13 on which the filling container 12 is placed. The filling container 12 is fitted into an opening (not shown) provided in the movable table 13 and placed almost horizontally on the movable table 13, and its upper surface 12b forms an almost horizontal plane.
[0035] The moving table 13 is attached with the moving means 14 via wheels 13a and a rod 14a, and is placed on a base 15 such as a rail. The rod 14a is also connected to a rotation mechanism (not shown), and by driving the rotation mechanism, the rod 14a rotates about its axis, and the moving table 13 also rotates integrally with the rod 14a. To move the movable table 13, for example, the rod 14a may be a rack, a pinion may be provided on the moving means 14, and the pinion may be rotated in both forward and reverse directions by a motor (not shown), thereby moving the movable table 13 in the left-right direction in Fig. 1 on the base 15. A single-axis robot or a fluid cylinder may be used as the moving means 14.
[0036] The hopper 11 has an internal space 11a, and the upper part is open from which the resin composition A of the present invention is poured. A long and narrow rectangular supply port 11b is provided at the bottom of the hopper 11. The supply port 11b may be provided with an opening / closing lid 11c that can be opened and closed by sliding, for example. Supply port 11b is located a predetermined distance, for example, about 0.1 to 1 mm above upper surface 12b of filling container 12, and is configured so as to be able to scrape over upper surface 12b. If the resin composition A has lumps, the filled resin composition A may have unevenness, so in order to prevent this, a mesh screen may be provided at the supply port 11b. The hopper 11 is supported by a support (not shown) and is configured to be vibrated in a horizontal plane as shown by the arrow in Fig. 1 by a vibrator (not shown) provided on the support, the hopper 11, etc. As the vibrator, a rotary vibrator, a piston vibrator, etc. can be used.
[0037] As shown in FIG. 2, the filling container 12 has an uneven pattern 12a formed thereon that corresponds to the grooves of the fuel cell separator and that takes into account the thickness distribution and approximates the volume ratio of the thick and thin portions of the fuel cell separator. The material of the filling container 12 may be the same as that of the mold for the fuel cell separator. However, since no pressure is applied by pressing, it is sufficient that the resin composition A does not deform when heated near its melting point and has heat resistance enough to withstand that temperature. Also, considering transportation during heating and charging, a lightweight material is preferred. Furthermore, when heated by a heater or the like, a material with high thermal conductivity is preferred in order to evenly distribute heat to the resin composition A. Considering these points, for example, a dense filling container made of aluminum or the like is preferred.
[0038] The opening width w, outer width W of the filling container 12, and length L of the supply port 11b of the hopper 11 are usually set such that w ≦ L < W. When arranging the filling container 12, the supply port 11b straddles the opening of the filling container 12. This is because if L < w, the resin composition A will not enter the filling container 12 evenly, and if W < L, the resin composition A will spill outside the filling container 12, resulting in a lot of waste. However, depending on various process conditions, it may be necessary to set L < w.
[0039] When filling the resin composition A into the filling container 12, first, place the filling container 12 so that the open end of the filling container 12 is located approximately at the center of the supply port 11b of the hopper 11, and then charge the resin composition A into the hopper 11. At this time, by vibrating the hopper 11 in the left - right direction of FIG. 2 with a vibrator (not shown), the internal resin composition A can smoothly fall without getting stuck on the way.
[0040] When the resin composition A is charged into the hopper 11, the resin composition A falls and is filled in the lower part of the supply port 11b in the filling container 12, and the resin composition A in the space 11a of the hopper accumulates on it. From this state, when the moving table 13 moves in the direction of the arrow in FIG. 1 while filling the resin composition A in the hopper 11 into the filling container 12, the excess resin composition A is scraped off at the supply port 11b of the hopper 11 to fill the resin composition A so that the upper surface is flat. A scraping plate (not shown) may be provided for the purpose of scraping at the upper surface 12b of the filling container 12. When filling container 12 has finished passing under supply port 11b, the space of filling container 12 in which concave and convex pattern 12a is formed is filled with resin composition A as shown in FIG. 3(a).
[0041] Thereafter, if necessary, the filling container 12 may be placed on a heating table (not shown), and the resin composition A may be heated to a temperature higher than the melting point of the epoxy resin and lower than its hardening point using a heating device such as a heater, and the resin composition A may be temporarily molded by maintaining this state. If the heating temperature is too low, the resin will not melt and temporary molding will not be possible, whereas if the heating temperature is too high, hardening will begin, causing uneven molding (such as sparseness). The heating temperature is preferably Tm to Tm+50°C, more preferably Tm to Tm+20°C, where Tm is the melting point.
[0042] After the provisional molding, the resin contained in the resin composition A is partially melted and the particles are lightly welded together, and the resin composition A does not immediately fall out even if the filling container 12 is turned upside down. In the case of a powder, it is difficult to pour the resin composition A into a mold all at once, but by carrying out the provisional molding, it is possible to pour the resin composition A, the particles of which are lightly welded together, all at once, and it is easy to pour it uniformly. The degree of adhesion between the particles after the preliminary molding may be such that some of the resin has melted and the particles are just barely able to hold themselves back when the filled container 12 is inverted, or such that all of the resin has melted and become one body, and the particles will break when a strong stress is applied but will not break or break if a small stress is applied; however, it is preferable that the particles are just barely able to hold themselves back when the filled container 12 is inverted.
[0043] Next, the moving means 14 moves the moving table 13, and as shown in Fig. 3(b), the filled container 12 filled with the resin composition A is brought directly above the lower mold 21 for molding on which the pattern 21a is formed, and accurately positioned using a positioning pin or the like, and the rod 14a is rotated by a rotation mechanism (not shown) to turn the filled container 12 upside down together with the moving table 13, and the resin composition A is dropped onto the lower mold 21 for molding. Even if the resin composition A is only fused to the extent that it will crumble if an attempt is made to remove it from the filled container 12, and it cannot be removed directly from the filled container 12, this method allows it to be evenly poured into the mold. Then, as shown in FIG. 3(c), the upper mold 22 on which the pattern 22a is formed is lowered, and pressure and heat are applied under the compression molding conditions described above to compress the thickness to a fraction of the original thickness, resulting in the fuel cell separator 1 shown in FIG. 3(d).
[0044] The fuel cell separator 1 thus obtained has a pattern 1a that forms the grooves, and has two regions with different thicknesses, a thick region and a thin region. The thin region corresponds to the bottom of the groove, and the thick region is the region between the grooves. In this case, it is preferable that the thick region and the thin region of the fuel cell separator 1 have the same density.
[0045] Next, the relationship between the depth of the pattern formed in filling container 12 and the thickness of fuel cell separator 1 will be described. FIG. 4 is a diagram for explaining a case where a filling container (not shown) on which no pattern is formed is used. As shown in FIG. 4(a), patterns 21a, 22a for forming grooves of a fuel cell separator 1' are formed on an upper mold 22 and a lower mold 21. When no pattern is formed on the filling container, as shown in FIG. 4(a), a resin composition A having a certain thickness is placed between the upper mold 22 and the lower mold 21, and pressure and heat are applied to produce a fuel cell separator 1'. In this case, as shown in FIG. 4(b), the density of the thin wall portion becomes high and the density of the thick wall portion becomes low.
[0046] Therefore, in this embodiment, a pattern 12a of protrusions and recesses is formed on the filling container 12 as shown in Fig. 2. Then, as shown in Fig. 3(d), the thickness of the thick portion of the resulting fuel cell separator 1 is m, the thickness of the thin portion is n, and as shown in Fig. 3(a), the relationship between M, N, m, and n is set to M:N ≈ m:n, where M is the depth of the deep portion of the pattern 12a of the filling container 12, and N is the depth of the shallow portion. In this way, protrusions and recesses approximating the volume ratio of the thick portion to the thin portion of the fuel cell separator can be formed on the filling container, and the filling container can be filled with a mass having a volume ratio approximating the volume ratio of the thick portion to the thin portion of the fuel cell separator.
[0047] In this embodiment, the uneven pattern 12a of the filling container 12 is formed based on this idea, so that the completed fuel cell separator 1 does not have uneven density, and a uniform molded body can be obtained.
[0048] Pattern 1a of fuel cell separator 1 and pattern 12a of filling container 12 may be the same, but if pattern 1a is fine, it is not necessary to form the same pattern as pattern 1a on filling container 12. If the same pattern is formed faithfully, problems may occur when the filling container 12 is inserted into the mold, such as the filling container not being smoothly inserted into the mold, resulting in some of the resin composition A remaining in filling container 12. If pattern 1a is fine, it is possible to mold a fuel cell separator with a nearly uniform density by, for example, taking the average value of multiple irregularities.
[0049] In this manner, in the above embodiment, for example, by using a dense filling container, the resin composition A is simply heated and provisionally molded without being pressurized, so that a large-scale device for pressing the resin composition A is not required, and it is possible to reduce the manufacturing cost of the fuel cell separator and to improve the production efficiency. Furthermore, since there is no direct manual operation, it is possible to eliminate concerns about the inclusion of impurities and a decrease in yield due to damage to the provisionally molded product. Furthermore, the resin composition A can be evenly poured into the filling container 12, and there is no unevenness in density in the fuel cell separator 1, so that the completed fuel cell separator 1 does not warp and has little unevenness in thickness.
[0050] Furthermore, without using a filling container, a fuel cell separator without uneven density can also be produced by pouring the resin composition into a fuel cell separator mold in a volume ratio that approximates the volume ratio of the thick and thin portions of the fuel cell separator.
[0051] In the present invention, the fuel cell separator (molded body) obtained by the above compression molding may be subjected to a surface roughening treatment for the purposes of removing the skin layer, adjusting the surface roughness, and the like. The roughening treatment method is not particularly limited and may be appropriately selected from various conventionally known roughening methods such as blasting and polishing. Air blasting, wet blasting, barrel polishing, and brush polishing are preferred, blasting using abrasive grains is more preferred, and wet blasting is even more preferred.
[0052] In this case, the average particle size (d=50) of the abrasive grains used in the blasting treatment is preferably 3 to 30 μm, more preferably 4 to 25 μm, and even more preferably 5 to 20 μm. The material of the abrasive grains used in the blasting process is not particularly limited, and for example, alumina, silicon carbide, zirconia, glass, nylon, stainless steel, etc. can be used, and these can be used alone or in combination of two or more types. The discharge pressure during wet blasting cannot be generally defined since it varies depending on the particle size of the abrasive grains, but is preferably 0.1 to 1 MPa, and more preferably 0.15 to 0.5 MPa. EXAMPLES
[0053] The present invention will be described in more detail below with reference to examples, comparative examples and test examples, but the present invention is not limited to the following examples. Note that the various physical properties in the following examples were measured by the following methods. (1) Measurement of loose bulk density of carbon powder, loose bulk density, compaction degree of resin composition The loose bulk density of the carbon powder, and the loose bulk density, hardened bulk density and compressibility of the resin composition were measured using a powder tester PT-S manufactured by Hosokawa Micron Corporation. (2) Measurement of the amount of volatile matter in a resin composition with a boiling point of 100°C or less The volatile matter contained in the resin composition and having a boiling point of 100° C. or less was measured by an infrared moisture meter FD-660 manufactured by Kett Electric Laboratory, Ltd., under conditions of holding the temperature at 110° C. for 10 minutes. (3) Measurement of particle size of molding resin composition The resin composition for fuel cell separators was melt-kneaded, cooled and solidified, and pulverized to obtain a molding resin composition, whose average particle size was measured in a wet manner using a particle size distribution measuring device (MT3000, manufactured by Microtrack Bell Co., Ltd.). (4) Measurement of filling time of resin composition Using the filling device shown in FIG. 1, the time taken for the resin composition to be filled into a filling container having dimensions of 300 mm length×400 mm width×3 mm depth was measured. The time measurement started when the resin composition in the hopper began to fill the filling container, and ended when the resin composition filled the space in the filling container. (5) Evaluation of variation in filling mass of resin composition Using the filling device shown in Figure 1, a filling container with a size of 300 mm length × 400 mm width × 3 mm depth was filled with the resin composition, the filling mass was measured, and the filling mass variation after 100 repetitions was evaluated using the following formula. The reference mass was 200 g. Filling mass variation (%) = (maximum filling mass - minimum filling mass) / reference mass (6) Evaluation of thickness unevenness in fuel cell separators The thickness of the fuel cell separator was measured at 20 points with a micrometer, and the thickness unevenness was evaluated using the following formula. Thickness unevenness (μm) = Maximum thickness of fuel cell separator - Minimum thickness of fuel cell separator (7) Evaluation of contact resistance of fuel cell separator (i) Carbon paper + separator sample Two of the prepared fuel cell separators were stacked together, carbon paper (Toray Industries, Inc., TGP-H060) was placed on the top and bottom of them, and copper electrodes were placed on the top and bottom of those. A surface pressure of 1 MPa was applied in the vertical direction, and the voltage was measured using the four-terminal method. (ii) Carbon paper Copper electrodes were placed above and below the carbon paper, a surface pressure of 1 MPa was applied in the vertical direction, and the voltage was measured using the four-terminal method. (iii) Contact resistance calculation method The voltage drop between the separator sample and the carbon paper was determined from the voltage values determined in (i) and (ii) above, and the contact resistance was calculated according to the following formula. Contact resistance (mΩ cm 2 ) = (voltage drop x contact area) / current
[0054] [1] Production of resin composition for fuel cell separator [Example 1-1] An epoxy resin component consisting of 20.4 parts by mass of epoxy resin (ortho-cresol novolac type epoxy resin, epoxy equivalent 198 g / eq), 10.7 parts by mass of phenolic resin (novolac type phenolic resin, hydroxyl group equivalent 103 g / eq), and 0.25 parts by mass of 2-phenylimidazole was charged into a Henschel mixer and mixed at 800 rpm for 3 minutes to prepare a mixture. The resulting mixture was melt-kneaded at 70°C for 3 minutes using a pressure kneader (MS-type small pressure kneader, manufactured by Nippon Spindle Manufacturing Co., Ltd. (formerly Moriyama Co., Ltd.)), and then the kneaded mixture was pulverized to 500 μm or less using a grinder (Power Mill, manufactured by Dalton Co., Ltd.) to produce a resin composition for fuel cell separators.
[0055] [Example 1-2] A resin composition for a fuel cell separator was produced in the same manner as in Example 1-1, except that the mixture was melt-kneaded using a twin-screw continuous kneader (S1KRC kneader, manufactured by Kurimoto, Ltd.) instead of a pressure kneader.
[0056] [Examples 1-3] The same graphite 1 as in Example 1-1, the epoxy resin component, and 150 parts by mass of methyl ethyl ketone were charged into a Henschel mixer and mixed at 800 rpm for 3 minutes to prepare a mixture. The resulting mixture was dried at 40° C. for 2 hours and then pulverized to 500 μm or less to prepare a resin composition for fuel cell separators.
[0057] [Examples 1-4] A resin composition for a fuel cell separator was produced in the same manner as in Example 1-1, except that graphite 2 (loose bulk density: 0.40 g / cc) was used instead of graphite 1.
[0058] [Examples 1-5] A resin composition for a fuel cell separator was produced in the same manner as in Example 1-1, except that graphite 3 (loose bulk density: 0.48 g / cc) was used instead of graphite 1.
[0059] [Examples 1-6] A resin composition for a fuel cell separator was produced in the same manner as in Example 1-1, except that graphite 4 (loose bulk density: 0.52 g / cc) was used instead of graphite 1.
[0060] [Examples 1-7] A resin composition for a fuel cell separator was produced in the same manner as in Example 1-1, except that graphite 5 (loose bulk density: 0.60 g / cc) was used instead of graphite 1.
[0061] [Examples 1-8] A resin composition for a fuel cell separator was produced in the same manner as in Example 1-1, except that graphite 6 (loose bulk density: 0.70 g / cc) was used instead of graphite 1.
[0062] [Examples 1-9] A resin composition for a fuel cell separator was produced in the same manner as in Example 1-8, except that the mixture was melt-kneaded in the same twin-screw continuous kneader as in Example 1-2, instead of in the pressure kneader.
[0063] [Examples 1-10] A mixture was prepared in the same manner as in Example 1-1 using graphite 8 (loose bulk density 0.73 g / cc) instead of graphite 1, and a resin composition for fuel cell separators was produced without subjecting the mixture to granulation such as kneading (melt kneading and pulverization).
[0064] [Examples 1-11] The mixture of Example 1-10 was melt-kneaded at 70° C. using the same twin-screw continuous kneader as in Example 1-2, and the kneaded product was then pulverized to 500 μm or less to prepare a resin composition for fuel cell separators.
[0065] [Comparative Example 1-1] A resin composition for a fuel cell separator was produced in the same manner as in Example 1-1, except that graphite 7 (loose bulk density: 0.33 g / cc) was used instead of graphite 1.
[0066] [Comparative Example 1-2] A resin composition for a fuel cell separator was prepared in the same manner as in Comparative Example 1-1, except that melt kneading was performed at 70° C. using the same twin-screw continuous kneader as in Example 1-2, instead of the pressure kneader.
[0067] [Comparative Example 1-3] A resin composition for a fuel cell separator was prepared in the same manner as in Example 1-11, except that the melt-kneading was carried out for 3 minutes at 70° C. using the same pressure kneader as in Example 1-1, instead of the twin-screw continuous kneader.
[0068] [Comparative Example 1-4] A resin composition for a fuel cell separator was produced in the same manner as in Comparative Example 1-2, except that graphite 7 in Comparative Example 1-2 was changed to graphite 9 (loose bulk density: 0.82 g / cc).
[0069] [Comparative Example 1-5] An epoxy resin component consisting of 20.4 parts by mass of epoxy resin (ortho-cresol novolac type epoxy resin, epoxy equivalent 198 g / eq), 10.7 parts by mass of phenolic resin (novolac type phenolic resin, hydroxyl group equivalent 103 g / eq), and 0.25 parts by mass of 2-phenylimidazole and 150 parts by mass of methyl ethyl ketone was charged into a Henschel mixer and mixed at 800 rpm for 3 minutes to prepare a mixture. The resulting mixture was dried at 40° C. for 2 hours, and then the kneaded product was pulverized to 500 μm or less to prepare a resin composition for fuel cell separators.
[0070] [Comparative Example 1-6] A resin composition for a fuel cell separator was prepared in the same manner as in Example 1-1, except that a roller compactor (Roller Compactor FT105, manufactured by Freund Corporation) was used instead of the pressure kneader.
[0071] [Comparative Example 1-7] A resin composition for a fuel cell separator was produced in the same manner as in Example 1-1, except that the mixture was not kneaded in a pressure kneader.
[0072] The above examples and comparative examples are summarized in Table 1.
[0073] [Table 1]
[0074] The resin compositions for fuel cell separators prepared in Examples 1-1 to 1-11 have a compression ratio of 14.0 to 40.0%, and the content of volatile components having a boiling point of 100°C or less is adjusted to less than 1.00 mass%. Therefore, compared with the resin compositions for fuel cell separators for molding prepared in Comparative Examples 1-1 to 1-2 and 1-4 to 1-7, the filling time into a filling container is shorter, and the variation in filling mass is also smaller than in Comparative Examples 1-1 to 1-7.
[0075] [2] Manufacturing of fuel cell separator molded bodies [Example 2-1] The fuel cell separator resin composition obtained in Example 1-1 was used to obtain a fuel cell separator molded article by the following method. 1) Using the filling device shown in Figure 1, fill a dense filling container with dimensions of 300 mm length x 400 mm width x 3 mm depth, which has irregularities similar to the volume ratio of the thick and thin parts of a fuel cell separator. 2) Next, the container containing the resin composition is heated at 75°C for 1 minute, 3) Next, the container filled with the resin composition is turned upside down directly above the fuel cell separator mold to pour the resin composition into the mold, 4) Compression molding was performed under conditions of a mold temperature of 185°C, molding pressure of 36.6 MPa, and molding time of 30 seconds to obtain a dense green body (a green body for fuel cell separators measuring 300 mm in length x 400 mm in width x 1 mm in thickness). The entire surface of the obtained fuel cell separator molded body was roughened by wet blasting using an alumina abrasive (average particle size: d50 = 6 μm) at a discharge pressure of 0.25 MPa and a conveying speed of 1.5 m / min to obtain a fuel cell separator.
[0076] [Examples 2-2 to 2-11, Comparative Examples 2-1 to 2-7] The resin compositions for fuel cell separators obtained in Examples 1-2 to 1-11 and Comparative Examples 1-1 to 1-7 were each compression molded in the same manner as in Example 2-1, and the entire surfaces of the resulting fuel cell separator molded bodies were roughened in the same manner as in Example 2-1 to obtain fuel cell separators.
[0077] The thickness unevenness and contact resistance of the resulting fuel cell separator were measured by the methods described above. The results are shown in Table 2.
[0078] [Table 2]
[0079] It is clear that the fuel cell separators obtained in Examples 2-1 to 2-11 have thickness variations of less than 50 μm and low contact resistance.
[0080] [Test Example 1-1] The resin composition for fuel cell separator obtained in Example 1-1 was directly poured into a fuel cell separator mold, and then compression molded under conditions of a mold temperature of 185°C, a molding pressure of 36.6 MPa, and a molding time of 30 seconds to obtain a molded body for fuel cell separator. Next, the entire surface of the obtained fuel cell separator molded article was subjected to a surface roughening treatment in the same manner as in Example 2-1 to obtain a fuel cell separator.
[0081] The thickness unevenness and contact resistance of the resulting fuel cell separator were measured by the above-mentioned methods. The results are shown in Table 2 together with the results of Example 2-1.
[0082] [Table 3]
[0083] The fuel cell separator of Example 2-1 was produced by filling a filling container with the resin composition for fuel cell separators and then putting it into a mold, and therefore had less unevenness in thickness and lower contact resistance than Test Example 1-1. [Explanation of symbols]
[0084] 1. Fuel cell separator 10 Filling equipment 12 Filling container 21 Lower mold (mold for fuel cell separator) 22 Upper mold (mold for fuel cell separator) A. Resin composition for fuel cell separator
Claims
1. A resin composition for a fuel cell separator, comprising: graphite powder; and an epoxy resin component including a base agent, a curing agent, and a curing accelerator; wherein the degree of compression calculated by the following formula is 14.0 to 40.0%, and the content of volatile components having a boiling point of 100°C or less is less than 1.00 mass%. Compressibility (%)=100×(solid bulk density of resin composition−loose bulk density of resin composition) / solid bulk density of resin composition
2. 2. The resin composition for a fuel cell separator according to claim 1, wherein the resin composition has a loose bulk density of 0.40 to 0.90 g / cc.
3. 2. The resin composition for a fuel cell separator in accordance with claim 1, wherein the graphite powder has a loose bulk density of 0.35 to 0.70 g / cc.
4. 2. The resin composition for fuel cell separator according to claim 1, wherein the base resin is at least one selected from an orthocresol novolac type epoxy resin having an epoxy equivalent of 194 to 215 g / eq and a biphenyl type epoxy resin having an epoxy equivalent of 180 to 200 g / eq.
5. 2. The resin composition for fuel cell separators according to claim 1, wherein the curing agent is a phenol novolac resin having a hydroxyl equivalent of 103 to 106 g / eq.
6. 2. The fuel cell separator resin composition according to claim 1, wherein the curing accelerator is an imidazole compound having a phenyl group at the 2-position.
7. The resin composition for a fuel cell separator is molded from a resin composition containing graphite powder, and an epoxy resin component containing a base agent, a curing agent, and a curing accelerator, and has a compression ratio of 14.0 to 40.0% calculated by the following formula, and a content of volatile components having a boiling point of 100°C or less of less than 1.00 mass%, and has a thickness unevenness of less than 50 μm and a contact resistance of 7.00 mΩ cm 2 A fuel cell separator, characterized in that Compressibility (%)=100×(solid bulk density of resin composition−loose bulk density of resin composition) / solid bulk density of resin composition
8. A method for manufacturing a fuel cell separator having thick and thin portions for forming grooves serving as gas flow paths on at least a portion of a surface thereof, comprising the steps of: The present invention relates to a method for manufacturing a fuel cell separator, the method comprising: pouring a resin composition for a fuel cell separator, the resin composition comprising graphite powder, and an epoxy resin component including a base agent, a curing agent, and a curing accelerator, the resin composition having a degree of compression calculated by the following formula of 14.0 to 40.0% and a content of volatile components having a boiling point of 100°C or less of less than 1.00 mass%, into a mold for a fuel cell separator such that the poured mass is a volume ratio that approximates the volume ratio of the thick portion to the thin portion of the fuel cell separator. Compressibility (%)=100×(solid bulk density of resin composition−loose bulk density of resin composition) / solid bulk density of resin composition
9. a step of filling the fuel cell separator resin composition into a filling container having projections and recesses formed thereon that have a volume ratio approximating that of a thick portion and a thin portion of the fuel cell separator; a step of inverting a container filled with the resin composition above a fuel cell separator mold to pour the resin composition into the mold; The method for producing a fuel cell separator according to claim 8 , further comprising the step of compression molding the resin composition poured into the mold.
Citation Information
Patent Citations
Electroconductive curing resin composition, its cured material, and its molded article
JP2002060639A
Manufacturing method of fuel cell separator
JP2006244937A
Method for manufacturing separator for fuel cell
JP2014112475A
Cellulose particles and cellulose particle dispersion
JP2023079480A